Benefits, Challenges, and Attitudes Toward ChatGPT in English Writing Courses at Saudi Universities - Alqahtani, Nasser (International Journal of Language and Literary Studies, 2024)
The purpose of this research is to gather the insights of students and teachers regarding the use and integration of ChatGPT in writing classes/courses at Saudi universities. By conducting a comprehensive review with the use of an online survey, the study is able to show the opportunities and risks posed by this technology. Using ChatGPT, it was found that the majority of the respondents have a slightly positive disposition toward the tool with a significant chunk of the responses leaning toward neutrality. The results show that the participants acknowledge the potential benefits of ChatGPT, citing increased creativity, improved learning experiences, academic support, and enhanced productivity as key benefits. Nonetheless, concerns such as the absence of a personal touch, plagiarism risks, and student anxiety were raised with teachers being more concerned about ethical considerations than students. The data indicate no constant high level of confidence in the use of ChatGPT, though, various participants commented that they required more training and guidance on the tool. The preference for using ChatGPT regularly or as a supplementary tool rather than to replace the traditional methods reflects cautious optimism towards its adoption. This study also shows with proper integration of the tool ChatGPT has great potential in writing classes to support students and educators, provided that educational institutions work on creating specific ethical guidelines, providing technical support, and ensuring academic integrity. This way, they can enjoy the benefits ChatGPT offers while managing the negative aspects and improving the overall educational experience. This research adds to the growing discussion regarding the use and integration of AI technologies in education contexts, and it offers a starting point for subsequent research that examines AI tool efficiency within Saudi educational environments.